Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah pada Kabupaten/Kota Provinsi Sumatera Barat Tahun Anggaran 2014-2016 - Andriani, Meri; Santi, Elfitri; Mustika, Rasyidah (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
This study aims to examine and analyze the influence of local government size, dependency level, age of local government, legislative size, population, regional income, functional differentiation and capital expenditure on the level of disclosure of local government financial reports to district/city regional governments in West Sumatra Province. The population of this study is the district/city regional government in West Sumatra Province with the sample used is the regional government financial report on the District/City Regional Government in West Sumatra Province for the period 2014-2016. The sample included in the criteria of this study were 57 local government financial reports using purposive sampling method. Data analysis method in this research uses multiple linear regression analysis with SPSS 20 program. The results of the research show that the legislative size and the number of population affect the level of disclosure of local government financial statements, but the size of the local government, the level of dependence, the age of local governments, regional income, functional differentiation and capital expenditure do not affect the level of disclosure of local government financial statements.